PENGARUH KONSEP DIRI, LINGKUNGAN TEMAN SEBAYA, DAN PENDAPATAN ORANG TUA TERHADAP PERILAKU KONSUMTIF MAHASISWA DENGAN PENGETAHUAN TEORI EKONOMI MIKRO SEBAGAI VARIABEL INTERVENING - Sri Purwaningsih; Vinus Maulina; Riril Mardiana Firdaus (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2017)
Needs are not limited demands to always think rationally to consume. This study discusses: (1) The indirect effect of self-concept to consumer behavior of students with the knowledge of microeconomic theory as an intervening variable, (2) The indirect effect peer environment to consumer behavior of students with the knowledge of microeconomic theory as an intervening variable, (3) the indirect effect of parents income to consumer behavior of students with the knowledge of microeconomic theory as an intervening variable. Research conducted at the University of Kanjuruhan Malang with subject 160 economic education students generation in 2013 – 2015 and sampling using proportional random sampling method was 48 students. The instrument use questionnaire. The result showed that there is an indirect effect between self-concept to consumer behavior (-0.054) with knowledge of economic theory as an intervening variable. Peer environment has indirect influence to consumer behavior (-0.319) with knowledge of economic theory as an intervening variable. While the parents income has a direct influence to consumer behavior at 0.239